Recent advances in the mechanisms of PD-L1 expression in gastric cancer: a review - Peifeng Chen; Zhangming Chen; Wannian Sui; Wenxiu Han (Biological Research)
Abstract In the progression of gastric cancer (GC), various cell types in the tumor microenvironment (TME) exhibit upregulated expression of programmed death ligand 1 (PD-L1), leading to impaired T-cell function and evasion of immune surveillance. Infection with H. pylori and EBV leads to increased PD-L1 expression in various cell types within TME, resulting in immune suppression and facilitating immune escape of GC cells. In the TME, mesenchymal stem cells (MSCs), M1-like tumor-associated macrophages (MI-like TAM), and myeloid-derived suppressor cells (MDSCs) contribute to the upregulation of PD-L1 expression in GC cells. Conversely, mast cells, M2-like tumor-associated macrophages (M2-like TAM), and tumor-associated neutrophils (TANs) exhibit elevated levels of PD-L1 expression in response to the influence of GC cells. Together, these factors collectively contribute to the upregulation of PD-L1 expression in GC. This review aims to provide a comprehensive summary of the cellular expression patterns of PD-L1 in GC and the underlying molecular mechanisms. Understanding the complex regulatory pathways governing PD-L1 expression may offer novel insights for the development of effective immunotherapeutic interventions.